Complete search strategies for "Teaching methods for integrating emotional intelligence in Bachelor of Science in Nursing Programs (2018-2024): An Integrative Review," Pestaner, et al. - Forbes, Carrie S. (My University, 2025)
The concept domains for this search included: "undergraduate nursing students," "nursing curriculum," and "emotional intelligence." Searches were performed in October 2024. Databases included: Medline via PubMed, PsycINFO via EBSCOhost, CINAHL via EBSCOhost, ERIC via ProQuest, and SCOPUS. Limiters used were five years (2018-2024).
Keywords: undergraduate nursing students; nursing curriculum; emotional intelligence; integrative review; search strings; search strategies